MODERN ANTIDEPRESSANTS BASED ON MEDICINAL PLANTS: RESEARCH IN A NATURAL DIRECTION - Турдыниязова Айтгуль Утениязовна (Web of Journals Publishing, 2025)
Depression is a prevalent psychiatric disorder worldwide, with limited efficacy and side effects of synthetic antidepressants. Therefore, medicinal preparations derived from plants are gaining great acceptance as a natural alternative. This article analyzes recent clinical studies on plants such as St. John's wort (Hypericum perforatum), saffron (Crocus sativus), lavender (Lavandula angustifolia), and curcuma (Curcuma longa). Mechanisms, efficacy, safety, and comparison of natural antidepressants with synthetic antidepressants are reviewed. In conclusion, it is emphasized that herbal antidepressants are promising as solitary and adjunctive therapy, but the need for large-scale, high-quality studies is highlighted.
Keywords: Herbal antidepressants, Hypericum perforatum, Crocus sativus, Curcuma longa, clinical trials, mechanism, side effects.